Enumeration and Identification of Surface Endophytes of Solanum lycopersicum and their Seasonal Recurrence - Abayneh, Lemma; Ayele, Abreham; Lamore, Tesfaye; Sebaro, Denebo; Srinivasan, Vijayalakshmir (Asian Journal of Biological and Life Sciences)
Background: Endophytes have been identified in various plant species; however, only a few studies have been conducted to explore the endophytic fungi folklore in fruit-bearing plants. The present study was conducted to enumerate the foliar endophytes of Solanum lycopersicum. Materials and Methods: The leaf samples of S. lycopersicum were harvested in four different seasons during the year 2020-2021. Samples were surface sterilized with 0.2% HgCl2, inoculated onto potato dextrose agar, amended with 0.12mg/ml chloramphenicol and incubated at 25-32°C with exposure to light and dark cycles. Identification was done by morphological typing. Results: Leaf samples harboured endophytes in all sampling seasons; however, season Sept-Nov which observed higher rainfall, witnessed more endophytes than the other seasons. The diversity of endophyte assemblage identified were hyphomycete and coelomycete species. Geotrichum sp., Phomopsis sp., Trichoderma sp., and Humicola sp. have proven their recurrence. Colletotrichum sp., being the dominant genus with higher colonization frequency, was found to be harboured in all sampling seasons. Conclusion: The study is the first of its kind in exploring the fungal endophytic profile in S. lycopersicum. Hence further studies are warranted to explore if the inherent endophytes of this plant confer any role in the metabolic physiology of the plant or host-pathogen interaction.
Keywords: Coelomycete; Colletotrichum; Endophyte; Solanum lycopersicum; Sporulation